Incidental finding of inflammatory fibroid polyp of the appendix in a patient with acute appendicitis - Alexander M. Sy; Duc Vo; David Friedel; James Grendell; Iman Hanna (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Sy AM, Vo D, Friedel D, Grendell J, Hanna I. Incidental finding of inflammatory fibroid polyp of the appendix in a patient with acute appendicitis. Turk J Gastroenterol 2020; 31(11): 831-34.